Pentingnya Pendidikan Seni dan Budaya dalam Pembentukan Identitas Siswa Sekolah Dasar - Habibi Musa (Journal of Humanities, Social Sciences, and Education, 2025)
Arts and culture education plays an important role in the formation of elementary school students' identities as a foundation for personal and social development. This literature study aims to analyze and summarize various studies related to how arts and culture education can shape students' characters, values, and identities in the early stages of education. Using the literature study method, this article examines various relevant research sources and theories from journals, books, and scientific articles. The results of the study indicate that arts and culture education contributes to increasing self-confidence, creativity, understanding of local and national cultural values, and forming attitudes of tolerance and empathy among students. Arts education also plays a role as a medium for introducing national identity and increasing love for native culture. In addition, this education supports harmonious cognitive and emotional development. This study concludes that the integration of arts and culture education in the elementary school curriculum is very important for forming strong and characterful student identities. The implications of this study point to the importance of improving the quality of arts and culture learning in a structured and contextual manner in the elementary education system.